2000
DOI: 10.1016/s0014-5793(00)02369-3
|View full text |Cite
|
Sign up to set email alerts
|

The gene encoding the NdhH subunit of type 1 NAD(P)H dehydrogenase is essential to survival of Synechocystis PCC6803

Abstract: The physiological function of the type 1 NAD(P)H dehydrogenase (Ndh-1) of Synechocystis sp. PCC6803 has been investigated by inactivating the gene ndhH encoding a subunit of the complex. Molecular analysis of independent transformants revealed that all clones were heteroploid, containing both wildtype and mutant ndhH copies, whatever the metabolic conditions used during genome segregation, including high CO 2 concentration. By replacing the chromosomal copy of the ndhH gene by a plasmidial copy under the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…It is unclear how the changed expression of this particular NDH subunit would influence the metabolism of M. aeruginosa, but an ndhK knock-out strain of Synechocystis sp. PCC 6803 demonstrated a decreased ability of cells to accumulate inorganic carbon (76). Such a response, where NdhK expression is low in toxic strains, but CcmK and CcmL proteins are highly expressed is consistent with the expected high-carbon requiring phenotype of microcystin-producers discussed above.…”
Section: Differential Display Between Toxic and Nontoxic Strains Of Msupporting
confidence: 76%
“…It is unclear how the changed expression of this particular NDH subunit would influence the metabolism of M. aeruginosa, but an ndhK knock-out strain of Synechocystis sp. PCC 6803 demonstrated a decreased ability of cells to accumulate inorganic carbon (76). Such a response, where NdhK expression is low in toxic strains, but CcmK and CcmL proteins are highly expressed is consistent with the expected high-carbon requiring phenotype of microcystin-producers discussed above.…”
Section: Differential Display Between Toxic and Nontoxic Strains Of Msupporting
confidence: 76%
“…We found that the protein levels of NdhH, NdhI, and NdhK, as well as the overall activity of NDH-1, increased significantly under low CO 2 conditions. Of these, NdhH is essential for the viability of the Synechocystis PCC6803 cells (Pieulle et al 2000). Inactivation of NdhK in this bacterium decreases CO 2 uptake activity to nearly zero and NdhK mutants were unable to grow under photoheterotrophic conditions (Ogawa 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This finding appears contradictory to the proposed role of NdhB in cyanobacterial inorganic carbon uptake and is inconsistent with the increase of NDH-1 activity at low CO 2 conditions. In an NdhB-defective mutant (M55), little or no NdhH, NdhJ or NdhK was found in either thylakoid or cytoplasmic membranes (Pieulle et al 2000), suggesting that the deficiency of NdhB led to an inability to assemble these subunits at thylakoid membrane. In addition, M55 cells showed severely flawed inorganic carbon uptake, which additionally suggests that inactivation of the ndhB gene in these cells may lead to disassembly of all NDH-1 complexes and the production of secondary phenotypes (Ohkawa et al 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al (2016) identified the new NdhV subunit in Synechocystis 6803 and proposed that NdhV cooperates with NdhS to accept electrons from Fd. In addition, ndhH gene was shown to be vital to the survival of Synechocystis 6803 even under high-CO 2 growth conditions (Pieulle et al, 2000). NdhJ was found in both plasma membrane and thylakoid membranes in Synechocystis 6803 (Berger et al, 1991;Pieulle et al, 2000) and Anacystis nidulans (Dworsky et al, 1995).…”
mentioning
confidence: 99%
“…In addition, ndhH gene was shown to be vital to the survival of Synechocystis 6803 even under high-CO 2 growth conditions (Pieulle et al, 2000). NdhJ was found in both plasma membrane and thylakoid membranes in Synechocystis 6803 (Berger et al, 1991;Pieulle et al, 2000) and Anacystis nidulans (Dworsky et al, 1995). The NdhN and NdhO subunits of Synechocystis 6803 were first identified by functional proteomics approach (Prommeenate et al, 2004;Battchikova et al, 2005).…”
mentioning
confidence: 99%